PHARMACOECONOMIC ASPECTS OF EPLERENONE USAGE IN CHRONIC HEART FAILURE - Yu. M. Lopatin; E. Yu. Lopatina (Кардиоваскулярная терапия и профилактика)
Eplerenone (Inspra, Pfizer) improves the prognosis of patients with chronic heart failure and heart failure after acute myocardial infarction. Since Russia eplerenone pharmacoeconomics issues rarely discussed, the analysis of the literature on this topic was performed. 2 studies examined effects of eplerenone in patients with chronic heart failure, 6 — in patients with heart failure after myocardial infarction. The only Russian study on pharmacoeconomics of eplerenone used data from studies in both groups. Due to distinctive methodology, currencies and date of publication, direct comparison of these studies is difficult.However, all studies have demonstrated the pharmacoeconomic benefits of eplerenone in patients with heart failure. A conclusion provided about the need for additional pharmacoeconomic studies of eplerenone in Russian Federation.